A Piercean Semiotic Analysis of The Indonesian Edition Cover of As Long As The Lemon Trees Grow - Ninik Hardianti; Myrna Nur Sakinah (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2025)
This study examines the Indonesian edition book cover of As Long As the Lemon Trees Grow, illustrated by Nadya Zahwa Noor, using Charles Sanders Peirce’s triadic semiotic framework. As book covers function as multimodal paratexts that shape reader expectations, analyzing their semiotic components allows a deeper understanding of how visual signs convey cultural, emotional, and narrative meanings. Employing a qualitative descriptive design, the study analyzes eight selected visual signs identified based on their visual salience, narrative relevance, and cultural symbolic significance within the cover composition. Each sign is examined through the relationship between representamen, object, and interpretant, and categorized as icon, index, or symbol. The findings reveal that the ornamental Middle Eastern–inspired frame, dominant blue and green color composition, lemon imagery and lemon trees, the silhouetted male and female figures, and their spatial arrangement collectively construct a layered visual discourse of hope, identity, conflict, and resilience. These elements simultaneously index Syrian cultural aesthetics and generate new symbolic meanings within the Indonesian interpretive context. The study demonstrates that the localized cover operates as a culturally adaptive semiotic artifact, illustrating how visual design mediates between global narrative identity and local readership. Through this analysis, the research contributes to broader discussions on visual semiotics, multimodality, and cultural adaptation in global publishing practices.